2000
DOI: 10.1677/joe.0.1660579
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory alterations of insulin signal transduction in liver of growth hormone receptor knockout mice

Abstract: Growth hormone (GH) deficiency is associated with increased sensitivity to insulin, but the molecular mechanisms involved in this association are poorly understood. In the current work, we have examined the consequences of the absence of the biological effects of GH on the first steps of the insulin signaling system in vivo in liver of mice with targeted disruption of the GH receptor/GH binding protein gene (GHR-KO mice). In these animals, circulating insulin concentrations are less than 4 µIU/ml, and glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
75
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 50 publications
13
75
2
Order By: Relevance
“…In fact, the occurrence of fasting hypoglycemia has been demonstrated in GHD children (25) and adults (26). This notion has been further supported by studies using animal models such as dwarf rats (27) and GH receptorknockout mice (28). On the other hand, several researchers have recently reported that insulin resistance occurs in GHD subjects.…”
Section: Discussionmentioning
confidence: 87%
“…In fact, the occurrence of fasting hypoglycemia has been demonstrated in GHD children (25) and adults (26). This notion has been further supported by studies using animal models such as dwarf rats (27) and GH receptorknockout mice (28). On the other hand, several researchers have recently reported that insulin resistance occurs in GHD subjects.…”
Section: Discussionmentioning
confidence: 87%
“…In a previous study we have used mice lacking GH receptors to investigate the consequences of the absence of GH action on insulin sensitivity and insulin signaling (Dominici et al 2000). As an extension of this study, we have now investigated the effects of combined deficiency of GH and PRL and thyrotropin (TSH) on insulin sensitivity and insulin signaling.…”
Section: Introductionmentioning
confidence: 99%
“…These mice have a number of striking features that have been recently reviewed [2]. First, they are extremely insulin sensitive [3][4][5][6][7][8][9][10][11][12]. Further, circulating levels of glucose and glucagon are decreased at a young age but normalize with advancing age [6,12].…”
Section: Ghr-/-micementioning
confidence: 99%